Willingness to pay for birdsong - Anthony Higney; Charlotte Gerling; Claire Buchan; Simon Butler; Liam Crowther; Melissa Marselle; Eleanor Ratcliffe; Konrad Uebel; Nick Hanley (Ecological Economics, 2026)

Divergent Selection on Dispersal Targets Chemosensory and Neuronal Genes in Tribolium castaneum - Michael D. Pointer; Will J. Nash; Lewis G. Spurgin; Mark McMullan; Simon Butler; David S. Richardson (Molecular Ecology, 2026)
Dispersal is key to the life history, ecology and evolution of many organisms and important in pest invasiveness. However, the genetic architecture underlying variation in dispersal behaviour remains poorly understood outside of a few model species. We investigated the genomic basis of dispersal using artificial selection on replicated lines of Tribolium castaneum , a flour beetle, an emergent model system and an economically important agricultural pest. Combining whole‐genome resequencing with population‐level genotype–phenotype association analysis, we identify nine genomic regions and 42 genes associated with selection on dispersal. Identified candidate genes were significantly enriched for functions related to neuronal structure and function, as well as chemosensory behaviour and mating, suggesting that variation in dispersal is mediated by neural and chemosensory pathways. Our results demonstrate that dispersal propensity has a polygenic basis and support an interaction between dispersal and mating ecology in this system. These findings contribute to a deeper understanding of the genetic mechanisms driving dispersal evolution and its role in shaping eco‐evolutionary dynamics.

Chilling Consequences: Recruitment Failure of Four Native Fish Species in a Thermally Polluted, Regulated River - Laura E. Michie; James N. Hitchcock; Simon M. Mitrovic; Matthew Gordos; Gavin L. Butler (Fisheries Management and Ecology, 2026)
Cold water pollution (CWP), caused by the release of unseasonably cool water from the bottom of large reservoirs to downstream rivers, is an escalating global threat to riverine biodiversity that is exacerbated by future dam developments and climate change. This study examined the impact of CWP on native fish populations in the Severn River (NSW, Australia), downstream of a large reservoir. Long‐term data (2012–2024) revealed chronic CWP, with thermal regimes frequently below thresholds required for native fish spawning during the austral summer period. An aged population structure and chronic recruitment failure were evident in four native fish species. Additionally, native fish stocking efforts have resulted in limited success. We recommend both long‐term CWP mitigation and immediate adaptive management strategies, such as optimising stocking practices and opportunistic water management actions, as critical to sustaining native fish populations.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Corrigendum to “Improving lipid utilization and growth through lecithin inclusion in diets for giant grouper (Epinephelus lanceolatus)” [Anim. Feed Sci. Technol. 326 (2025) 116393] - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

Improving lipid utilization and growth through lecithin inclusion in diets for giant grouper (Epinephelus lanceolatus) - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

Dietary methionine and choline mediate mobilisation of plasma lipids to improve feed efficiency for the diets of giant grouper (Epinephelus lanceolatus) - Grace Butler; Caroline Lourdes Candebat; Simon Kumar Das; Leo Nankervis (Animal Feed Science and Technology, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

Traits Underlying Experimentally Evolved Dispersal Behavior in Tribolium castaneum - Michael D. Pointer; Lewis G. Spurgin; Ramakrishnan Vasudeva; Mark McMullan; Simon Butler; David S. Richardson (Journal of Insect Behavior, 2024)
Dispersal is an important behavior in many animals, with profound effects on individual fitness and the evolutionary trajectories of populations. This is especially true within taxa with particular life-history strategies, for example those that exploit ephemeral habitat. Further, dispersal is commonly seen to be part of behavioral syndromes - suites of traits that covary across behavioral contexts. The red flour beetle, Tribolium castaneum (Coleoptera, Tenebrionidae), is a major post-harvest crop pest responsible for large losses through the infestation of stored grain. In this system dispersal is known to have a strong genetic basis and differential artificial selection on dispersal traits produces strong phenotypic divergence. However, it is unknown which traits are able to rapidly evolve to produce these results, or which behavioral components underlie differences in dispersal. Using replicate lines of T. castaneum previously selected for divergent dispersal behavior, we test for correlated activity and movement patterns, morphology and substrate surface use. We find robustly repeatable associations between the dispersal phenotype and higher activity, straighter paths, larger body size (but not relative leg length) and increased tendency to remain at the surface of fodder. Together our results suggest that dispersal is part of a syndrome of traits in T. castaneum , and must be treated as such when considering the evolution of dispersal in this system, and in attempting to predict and control its spread.

Management practices, and not surrounding habitats, drive bird and arthropod biodiversity within vineyards - Natalia B. Zielonka; Jack D. Shutt; Simon J. Butler; Lynn V. Dicks (Agriculture, Ecosystems & Environment, 2024)

What makes a change agent in environmental conflict transformation? Evidence from rural France - Simon Calla; Lou Lécuyer; James R. A. Butler; Juliette C. Young (Biodiversity and Conservation, 2024)
Transformation of agriculture towards increased sustainability is needed to meet the challenge of declining biodiversity. Nevertheless, stakeholders’ differing perceptions of what sustainability should be, and the multiplicity of possible ways to achieve it can lead to conflictual situations, highlighting the importance of conflict transformation as part of the broader sustainability transformation. If conflict transformation needs to be addressed to prevent the status quo persisting, such processes also reveal the state of social relations and allow us to analyze how collective actions could lead to broader transformations. Using three case studies involving conflicts around pesticide use in the region Bourgogne Franche-Comté (France), we investigate the hypothesis that transformation processes require the engagement of change agents who are motivated and able to overcome barriers to change. Results from 55 in-depth interviews with stakeholders highlight that transformational change depends less on the capacities of a single individual, and more on the mobilization of a plurality of heterogeneous actors (especially farmers, local authorities, and the general public). These actors need to carry out a range of activities that occur with and for others and have an influence on others. According to interviewees, the actors need to engage others, encourage new initiatives, create spaces for knowledge exchanges, and go beyond boundaries. The effectiveness of change agents also depends on the existence of participatory and proactive processes to bring individuals together to create or capitalize on windows of opportunity.

Dhaka city water logging hazards: area identification and vulnerability assessment through GIS-remote sensing techniques - Rafiul Alam; Zahidul Quayyum; Simon Moulds; Marzuka Ahmad Radia; Hasna Hena Sara; Md Tanvir Hasan; Adrian Butler (Environmental Monitoring and Assessment, 2023)
Water logging is one of the most detrimental phenomena continuing to burden Dhaka dwellers. This study aims to spatio-temporarily identify the water logging hazard zones within Dhaka Metropolitan area and assess the extent of their water logging susceptibility based on informal settlements, built-up areas, and demographical characteristics. The study utilizes integrated geographic information system (GIS)-remote sensing (RS) methods, using the Normalized Difference Vegetation Water and Moisture Index, distance buffer zone from drainage streams, and built-up distributions to identify waterlogged zones with a temporal extent, incorporating social and infrastructural attributes to evaluate water logging effects. These indicators were integrated into an overlay GIS method to measure the vulnerability level across Dhaka city areas. The findings reveal that south and south-western parts of Dhaka were more susceptible to water logging hazards. Almost 35% of Dhaka belongs to the high/very highly vulnerable zone. Greater number of slum households were found within high to very high water logging vulnerable zones and approximately 70% of them are poorly structured. The built-up areas were observed to be increased toward the northern part of Dhaka and were exposed to severe water logging issues. The overall findings reveal the spatio-temporal distribution of the water logging vulnerabilities across the city as well as its impact on the social indicators. An integrated approach is necessary for future development plans to mitigate the risk of water logging.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Neurophysiological correlates of dual tasking in people with Parkinson’s disease and freezing of gait - Conor Fearon; John S. Butler; Saskia M. Waechter; Isabelle Killane; Simon P. Kelly; Richard B. Reilly; Timothy Lynch (Experimental Brain Research, 2021)

Judgements of hand location and hand spacing show minimal proprioceptive drift - Alex Rana; Annie A. Butler; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2020)

The hidden hand is perceived closer to midline - Hassan G. Qureshi; Annie A. Butler; Graham K. Kerr; Simon C. Gandevia; Martin E. Héroux (Experimental Brain Research, 2019)

Insights into the migration of the European Roller from ring recoveries - Tom Finch; Jamie Dunning; Orsolya Kiss; Edmunds Račinskis; Timothée Schwartz; Laimonas Sniauksta; Otto Szekeres; Béla Tokody; Aldina Franco; Simon J. Butler (Journal of Ornithology, 2017)

Short-interval cortical inhibition and intracortical facilitation during submaximal voluntary contractions changes with fatigue - Sandra K. Hunter; Chris J. McNeil; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2016)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

The origin of activity in the biceps brachii muscle during voluntary contractions of the contralateral elbow flexor muscles - Inge Zijdewind; Jane E. Butler; Simon C. Gandevia; Janet L. Taylor (Experimental Brain Research, 2006)